Ethics in the Gospel of John, Discipleship as Moral Progress. - Sookgoo Shin (Biblical Interpretation Series, 2019)
In Ethics in the Gospel of John Sookgoo Shin seeks to challenge the dominant scholarly view of John's ethics as an ineffective and unhelpful companion for moral formation. In order to demonstrate the relevance of John's ethics, Shin argues that the development of discipleship in John's Gospel should be understood as moral progress, which was a well-known moral concept in the ancient Mediterranean world. Having drawn an ethical model from the writings of Plutarch, this study aims to identify the undergirding ethical dynamic that shapes John's moral structure by bringing out the implicit ethical elements that are embedded throughout John's narratives, and thus suggests a way to read the whole Gospel ethically and appreciatively of its literary characteristics.